1998
DOI: 10.1126/science.279.5347.57
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical Properties of an Ultrathin Layer of Directionally Aligned Helical Polypeptides

Abstract: Electromechanical properties of an ultrathin layer of directionally aligned helical polypeptides Jaworek, T.; Neher, D.; Wegner, G.; Wieringa, R.H.; Schouten, A.J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 37 publications
2
107
0
2
Order By: Relevance
“…Furthermore, direct polar rod-like molecules have been suggested to assemble in a twisted-grain boundary mesophase that probably displays piezoelectric properties (Jaworek et al (1978); Vidal and Mello, 2001;Vidal, 2003). The expressive influence of a mechanical effect as is the exercise on the structure of the rat calcaneal tendon can be revealed by Fig.…”
Section: Morphological Considerationsmentioning
confidence: 96%
“…Furthermore, direct polar rod-like molecules have been suggested to assemble in a twisted-grain boundary mesophase that probably displays piezoelectric properties (Jaworek et al (1978); Vidal and Mello, 2001;Vidal, 2003). The expressive influence of a mechanical effect as is the exercise on the structure of the rat calcaneal tendon can be revealed by Fig.…”
Section: Morphological Considerationsmentioning
confidence: 96%
“…Jaworek et al studied the piezo-electric properties [47]. The field-induced change in film thickness were dominated by a inverse-piezoelectric effect and demonstrated that the helices were in a parallel arrangement.…”
Section: Pblg Monomolecular Filmsmentioning
confidence: 99%
“…Peptides of poly(α-benzyl-L-glutamate) (PBLG) are well known to form α-helical secondary structure stabilized by intramolecular hydrogen bonds [18]. The α-helical structure is thought to give rise to a rigid-rod structure, and PBLG has been employed as a typical model of rigid-rod building block in linear rod-coil block copolymers, for example, poly(ethylene oxide) [19], poly(N-isopropylacrylamide) [20], poly(dimethylsiloxane) [21], poly(styrene) (PS) [22], poly(butadiene) [23], poly(isoprene) (PI) [24], poly(fluorine) [25], and poly{2,5-bis[(4-methoxyphenyl)oxycarbonyl]styrene} [26] have been used so far as nonpeptide block.…”
Section: Introductionmentioning
confidence: 99%